2016
DOI: 10.1021/acs.jpcb.6b08160
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Dynamics of Ligand Binding to the Heme Domain of the Bacterial CO Sensor Protein RcoM-2

Abstract: The aerobic Gram-negative bacterium Burkholderia xenovorans expresses two highly homologous carbon monoxide (CO)-responsive transcriptional regulators, RcoM-1 and RcoM-2, which display extraordinarily high CO affinities, even under oxygenic conditions. To gain insight into the origin and perspectives of this feature, we characterized the ligand-binding properties of the N-terminal, heme-binding Per/Arnt/Sim sensor domain of RcoM-2 by time-resolved spectroscopy. We show that upon photodissociation of the heme-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(48 citation statements)
references
References 47 publications
2
46
0
Order By: Relevance
“…Non-exponential behavior and slowing down of ultrafast CO rebinding kinetics over a narrow range of increasing temperature has also been reported in other heme systems such as DNR, RrCooA and DosT 30 as well as for RcoM-2 31 . However, it has been suggested that the CO rebinding to these proteins involves no enthalpic barrier and the non-exponential behavior is attributed to a distribution of activation entropies 3031 .…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…Non-exponential behavior and slowing down of ultrafast CO rebinding kinetics over a narrow range of increasing temperature has also been reported in other heme systems such as DNR, RrCooA and DosT 30 as well as for RcoM-2 31 . However, it has been suggested that the CO rebinding to these proteins involves no enthalpic barrier and the non-exponential behavior is attributed to a distribution of activation entropies 3031 .…”
Section: Discussionmentioning
confidence: 53%
“…These and other studies have shown that a wide variety of heme proteins, including CooA proteins 6, 32 , nitrophorin 4 21 , CBS 33 , tr-HBO 34 , RcoM-2 31 and mutants of cytochrome c 35 rebind CO on the sub-nanosecond time scale with high geminate yield. In this report we explore the geminate rebinding kinetics of CO to ChCooA, over a broad temperature range (300 K to 20 K).…”
Section: Introductionmentioning
confidence: 64%
See 2 more Smart Citations
“…In general, free hemoglobin consists of two components, the organic and inorganic parts [96][97][98], where the inorganic heme iron complex of hemoglobin binds with oxygen O2 molecules [99][100][101], forming oxygen-heme iron complexes [102]. Interestingly, the association of oxygen O2 with the iron complex leads to a tense-to-relax structural change in the hemoglobin, altering oxygen O2 affinity of the free hemoglobin [103][104][105][106].…”
Section: Hemoglobin-loaded Hydrogelmentioning
confidence: 99%